Effectiveness of Therapeutic Plasma Exchange in Paediatric Atypical Haemolytic Uremic Syndrome: A Cohort Study in a Transplant Institute of Gujarat, India - Pooja Yuvraj Modi; Amitkumar Vishnubhai Prajapati; Kamal V Kanodia; Anshuman Saha; Kinnari B Vala (Journal of Clinical and Diagnostic Research)
Introduction: Atypical Haemolytic Uremic Syndrome (aHUS) is a rare but serious condition that primarily affects the kidneys, leading to kidney failure, anaemia, and low platelet counts (thrombocytopenia). Therapeutic Plasma Exchange (TPE) is the first-line treatment for aHUS, as stated in the American Society of Apheresis Guidelines (ASFA 2023), and is classified as a Category 1 indication. Aim: To determine whether TPE can be regarded as an effective treatment modality alongside conservative management in paediatric aHUS. Materials and Methods: This retrospective observational cohort study was conducted in the Department of Transfusion Medicine at the Institute of Kidney Diseases and Research Centre, Ahmedabad, Gujarat, India, between October 2023 and April 2024, involving paediatric patients with aHUS. Anti-Factor H antibody testing was performed to confirm the diagnosis; for some patients, the diagnosis was corroborated through clinical correlation by the treating paediatric nephrologists. The patients were then advised to undergo TPE in conjunction with conservative management. TPE was performed on the Com Tec, Fresenius Kabi, continuous cell separator apheresis machine after obtaining informed consent from the patients’ parents or guardians. Pre and post procedural haematological and renal parameters were recorded and analysed to study the recovery profile in each patient. The mean and standard deviation were calculated for all parameters using Microsoft Excel 2010, and certain data were analysed as percentages. A paired t-test was employed to assess the statistical significance of changes in pre and post exchange haemoglobin levels, platelet counts, and serum creatinine levels. Results: In the present study, 12 paediatric aHUS patients were evaluated for their response to TPE. Of these, the majority showed a positive response to TPE therapy, with 75% of patients (9 out of 12) achieving a complete response. Additionally, 16.66% (2 out of 12) exhibited a partial response to TPE therapy, while 8.33% (only 1 out of 12) showed no response to TPE therapy. Each patient underwent a minimum of eight and a maximum of 16 TPE procedures, culminating in a total of 133 procedures performed on the 12 patients. Adverse events were observed in 25.56% (34 out of 133) of the total TPE procedures. The most common adverse event was chills and rigors, which accounted for 47.05% (16 out of 34 events) of the total number of adverse events. Conclusion: In the present study, the clinical triad of the disease (haemoglobin levels, platelet count, serum creatinine) improved post-TPE in the majority of patients with aHUS. The adverse events were few and manageable with conservative treatment. It was observed that TPE can be regarded as an effective and safe therapeutic modality for treating paediatric aHUS patients. However, given the small sample size and retrospective nature of the study, more robust prospective studies and clinical trials are needed to draw general conclusions.